Ozone distribution in the lower troposphere over complex terrain in Central Chile. Issue 7 (3rd April 2013) - Seguel, Rodrigo J.; Mancilla, Carlos A.; Rondanelli, Roberto; Leiva, Manuel A.; Morales, Raúl G. E.
Abstract : [1] Observations were performed in 12 communities of Central Chile in order to determine the horizontal gradients of ozone in the Santiago Basin and surrounding valleys. Higher ozone mixing ratios were found northeast of the Santiago Basin and included east of the Aconcagua Valley (~70 km from Santiago) suggesting that photochemical pollution produced in Santiago is capable of passing through the Chacabuco mountain chain (~1.3 km) and have impact downwind from the regions with the largest NOx and VOC emissions. To complement existing surface observations, ozonesonde and tethersonde campaigns were performed in the Santiago Basin and the Aconcagua Valley. The results suggest ozone can accumulate in layers aloft (e.g., >102 ppb at 2 km) similarly to layers observed in complex topography coastal regions like Southern California. Layers of significant ozone concentrations having a near surface origin were observed above the mixed layer and below the subsidence inversion base. We propose that the ozone in this residual layer can be transported large distances (at least to 70 km) to further penetrate into the local environment under conditions of a well‐mixed boundary layer. Key Points: Elevated ozone concentration within the Residual Layer The role of the RL in the O3 transport Vertical profile of O3 within the Mixed Layer